2016
DOI: 10.1371/journal.ppat.1005626
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity as Consequence of a Microaerobic and Neutrophilic Lifestyle

Abstract: As a neutrophilic bacterium, Helicobacter pylori is growth deficient under extreme acidic conditions. The gastric pathogen is equipped with an acid survival kit, regulating urease activity by a pH-gated urea channel, opening below pH 6.5. After overcoming acid stress, the bacterium’s multiplication site is situated at the gastric mucosa with near neutral pH. The pathogen exhibits exceptional genetic variability, mainly due to its capability of natural transformation, termed competence. Using single cell analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 81 publications
1
35
0
Order By: Relevance
“…Indeed, since in most cases (92%) both daughter cells will display the fluorescent marker, integration is likely to occur before the replication of the locus. We cannot however rule out the possibility that, having incorporated large amounts of tDNA (Kruger et al ., ), two independent recombination events might have occurred. For the studies presented here the site of GFP insertion at the ureA locus ( hp0073 ) is relatively close to the origin of replication of the chromosome (Donczew et al ., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, since in most cases (92%) both daughter cells will display the fluorescent marker, integration is likely to occur before the replication of the locus. We cannot however rule out the possibility that, having incorporated large amounts of tDNA (Kruger et al ., ), two independent recombination events might have occurred. For the studies presented here the site of GFP insertion at the ureA locus ( hp0073 ) is relatively close to the origin of replication of the chromosome (Donczew et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…New microscopy approaches are emerging to better comprehend the mechanisms involved in the process of transformation. In recent times, several studies revealed the formation of tDNA foci on the surface of competent bacteria (Stingl et al, 2010;Berge et al, 2013;Gangel et al, 2014;Hahn et al, 2015;Kruger et al, 2016). Only one group followed by microscopy the tDNA passage into the cytoplasm .…”
Section: Introductionmentioning
confidence: 99%
“…The estimated mutation rate suggested a mutation burst during the acute infection phase that is over 10 times faster than the mutation rate during chronic infection, and orders of magnitude faster than mutation rates in any other bacteria ( Linz et al, 2014 ). Tracking of fluorescent DNA in competent bacteria has shown that H. pylori has the capacity to take up large quantities of DNA ( Kruger et al, 2016 ) and natural competence has been shown to promote chronic infection in a murine model of infection ( Dorer et al, 2013 ). The presence of multiple strains combined with natural competence may enable H. pylori to adapt to different environmental conditions in the stomachs of individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Based on its homology to the archetypal T4SS of A. tumefaciens , a two-step DNA uptake model has been proposed (Stingl et al 2010). The ComB T4SS facilitates double-stranded DNA uptake into the periplasm, and a second, ComEC system is then utilized to incorporate the periplasmic DNA across the cytoplasmic membrane and into the host cell (Stingl et al 2010; Kruger et al 2016). …”
Section: Dna Translocation Strategiesmentioning
confidence: 99%